•  Упростите выражение:

    а) 6 + 4а – 5а + а – 7а;

    б) 5(п – 2) – 6(п + 3) – 3(2п – 9);

Ответы 2

  • а)=6-7аб)=5п-10-6п-18-6п+27=-7п-1
    • Автор:

      rosendo
    • 5 лет назад
    • 0
  •  

    a) \ 6 + 4a - 5a + a - 7a = 6 + a(4 - 5 + 1 -7)= 6 - 7a\\\\ b) 5(p - 2) - 6(p+3) - 3(2p-9) = 5p - 10 - 6p - 18 - 6p + 27 =\\ p(5-6-6) + (27-10-18) = -7p - 1

     

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years